(3TQM GdeYdbGJ GdSHYs - (3dCHi LYaQ CMeO Hf ESeGYjd GdeQGOi GdeUQjs; (3MSjf Hf CMeO Hf MSjf GdRhRfj, CHh YHO Gddg,J (B486 (3g` s
(3ChdgG (B:s
(3GdPi LQi Ydjg CeQ CcKQ Cgd GddZI GdEcKGQ ai JaSjQ ZQjH GdTYQ hEYJbGd dWja eGajg ef GdfMh s
(3BNQgG (B:s
(3bGd dgG gd dc jGJGai bGdJ dg eG CfJ HGdeQVi BNQ GdeYdbGJ GdSHY hGdeVGaJjf EdjgG , TQM CHj GdLYaQ GdfMGS s
(3GdbUjOJGf (B: (3GddGejg ddCYTi hOY gQjQI hGdOGdjg ddfGHZI GdPHjGfi jGOGQ ejIs
(3GdhQbGJ GdChdi Hbde eZGjQs
(3HChdgG Jedc dCMeO Hf GdMSjf Hf CejQ GdeDefjfs
(3hJQLeI ddTGQM efbhdI s
(3HBNQgG CfgG bhHdJ HGdCUd Gdefbhd ajg s
(3HGdeYgO fSNJGf CNQjGf GfXQ ai GdLRA GdCh s
Keywords: (3GdCOHs